Efficacy of Kampo Medical Treatment Focused on Kami-syoyo-san against Premenstrual Syndrome (PMS) - KAWAGUCHI, Keiko; KUBO, Michinori; TAHARA, Eiichi; NAKAO, Kikuyo; MORIYAMA, Kenzou; SHINTANI, Takuhiro; NIIZAWA, Atsushi; NINOMIYA, Hiroyuki; TAKAYA, Yutaka; TSUKIOKA, Yasuyuki (Kampo Medicine, 2005)
Approximately 40% of women during the course of their menstrual cycles suffer from premenstrual syndrome (PMS). The cause of this syndrome is unknown, furthermore diagnostic criteria and treatments have not been established. Kampo medicines were applied using Kami-shoyo-san as a first choice, and several other alternative Kampo medicines, to 33 PMS patient cases. To evaluate the effectiveness of this therapy, PMS scores were recorded prior to treatment. Patients' scores were recorded as; score 0 (symptomless), score 1 (endurable), score 2 (unbearable without medicine), as well as the five major characteristics of PMS, 1) psychiatric symptoms, 2) headache, 3) breast pain, 4) swelling, 5) lower abdominal pain or lumbago. The scores were verified subsequent to two menstrual cycles. Kampo medicine was found to be effective in 24 cases, with scores declining in average from 4.4 to 1.5. Further treatments were requested in 4 cases, moreover, 5 cases were discounted altogether. Thus Kampo medicine proved to be a very useful method for patients suffering from PMS.